On The Issue Of Language Interference At Language Levels In The Study Of A Tertiary Language (Texas Journal of Philology, Culture and History, 2024)
This paper investigates the phenomenon of language interference in the context of tertiary language acquisition, focusing on how previously learned languages impact the learning of a new language. It examines interference at various linguistic levels, including phonology, morphology, syntax, and semantics, identifying common patterns and challenges faced by learners. The study explores the role of both the learner's first (L1) and second language (L2) in shaping interference patterns, considering factors such as typological similarity and proficiency levels. We analyze the impact of language interference on both receptive and productive language skills, emphasizing the need for explicit awareness strategies and targeted pedagogical interventions. The research aims to provide valuable insights into the complexities of tertiary language learning, offering implications for language teaching practice and curriculum development.